2017
DOI: 10.1371/journal.pone.0190217
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor dependent collagen gene expression induced by MAS agonist AR234960 in human cardiac fibroblasts

Abstract: Perspectives on whether the functions of MAS, a G protein-coupled receptor, are beneficial or deleterious in the heart remain controversial. MAS gene knockout reduces coronary vasodilatation leading to ischemic injury. G protein signaling activated by MAS has been implicated in progression of adaptive cardiac hypertrophy to heart failure and fibrosis. In the present study, we observed increased expression of MAS, connective tissue growth factor (CTGF) and collagen genes in failing (HF) human heart samples when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…Extracellular matrix remodeling during myocardial hypertrophy involves multiple enzymes and structural proteins (32), and our current study identified changes in RV FN, CTGF, COL1A1, and pulmonary FN without changes in collagen III or collagen IV. This may be due to a differential cardiac fibroblast synthetic response to hypertrophic stimuli (6,16,41,55). Our results are consistent with an important role for COL1A1 in PAH-associated RV fibrosis identified using a COL1A1 mutant mouse model that has attenuated RV fibrosis and dysfunction (69).…”
Section: Discussionsupporting
confidence: 88%
“…Extracellular matrix remodeling during myocardial hypertrophy involves multiple enzymes and structural proteins (32), and our current study identified changes in RV FN, CTGF, COL1A1, and pulmonary FN without changes in collagen III or collagen IV. This may be due to a differential cardiac fibroblast synthetic response to hypertrophic stimuli (6,16,41,55). Our results are consistent with an important role for COL1A1 in PAH-associated RV fibrosis identified using a COL1A1 mutant mouse model that has attenuated RV fibrosis and dysfunction (69).…”
Section: Discussionsupporting
confidence: 88%
“…In a study of keloid pathogenesis, increased Col production, cell proliferation, and migration of keloid fibroblasts were demonstrated to be suppressed by STAT3 short interfering (si)RNA (Lim et al, 2006). An in vivo and in vitro study of cardiac hypertrophy also showed that during induction of cardiac hypertrophy, treatment of fibroblasts with specific STAT3 inhibitors or STAT3 siRNA resulted in downregulation of IL-6-induced STAT3 phosphorylation and Col type 1 and type 3 gene expressions in cardiac fibroblasts (Chatterjee et al, 2017). In the present study, treatment with an anti-IL-6 antibody to neutralize exogenous IL-6 reduced the pSTAT3/STAT3 ratio (Figure 5b).…”
Section: Suppression Of the Il-6-stat3 Signaling Pathway To Prevent Digosupporting
confidence: 74%
“…In normal physiological states, collagen deposition and inflammatory response of heart tissue is devastatingly low, but it is significantly expanded and contributes to Ann Transl Med 2022 | https://dx.doi.org/10.21037/atm-21-6667 further damage in disease states, such as MI, cardiac hypertrophy, and heart failure (32,33). Thus, evaluation of histopathological changes in the cardiac tissue using Masson and H&E staining is necessary.…”
Section: Discussionmentioning
confidence: 99%